Pendekatan Rancang Kota pada Masalah Banjir Kota Palembang (Jurnal TekstuReka, 2023)
Flood in city of Palembang caused by many factors. Inadequate and unconnected city drainage channels, as well as the geomorphological condition of the city which is a lowland with rivers and swamps are the causes of flooding that routinely occurs. Various ways to overcome flooding have been done but still not effective, flooding still occurs and the losses incurred are also increasing. This paper took urban design as a tool to tackle flood problems without ignoring other technical aspects. The purpose of this research is to find the main problem of flood and then analyze it with urban context to get the effective solutions. The method which selected are literature and comparative study. The conclusion is the needed of a master plan of flood intervention, re-established green open space until 30% of total area, Fix the drainage system, install storm-water way system and reclaimed river, swamp as flood control.